Azobenzene-liquid crystal composite for fabrication of optical storage devices - Gan, Siew Mei (2015)
The primary purpose of this research is to characterized four series of azobenzene with different substituents to be employed as azobenzene-liquid crystal composite mixture in optical storage devices. Firstly, the azobenzene substituents effects on liquid crystallinity were observed under polarising optical microscope and their phase transition temperatures were confirmed by calorimetric study. After that, photoisomerisation studies were conducted in solution form by using UV–Vis spectrophotometer in order to measure the time required for cis–trans isomerisation in thermal back relaxation process. In azobenzene with fluorine addition, monofluoro azobenzene with ester functional group gave smectic-A and nematic phases with thermal back relaxation around 22 hours. Better results were obtained by azobenzene with olefinic terminal chain; the presence of alkene enhanced the thermal back relaxation to 45 hours due to the unsaturated bonding in the molecule, capable of photo-crosslinking. However, incorporation of group-17 elements such as fluorine, chlorine, bromine and iodine in the olefinic azobenzene shorten the thermal back relaxation time although smectic-A and nematic phases were generated. Prototype of optical storage devices created showed good stability with high contrast display due to their thermal back relaxation and mesophases. This study is a bold step to tailor the property of light-sensitive azobenzene to make them suitable for optical storage device applications. Presented data give rich information about structure property relations where one can able to control the molecular structure using light.